Ptoblematics of Involvement of Youth in Mass and Professional Sports Activities - Andrii Koval (Lesya Ukrainka Volyn National University, 2018)
Today the strategy of human development should predominate on a scale of the state. In fact the formation and the progress of the nation, and therefore of the state itself, are possible only if all the necessary favorable conditions for the self-development and self-realization of each individual are created. The author examines the current state of the development of sport and its relevance. The attention is focused on the development of sport, as one of the priority issues of state policy of Ukraine. The author covers thorny questions of problematics of involvement of youth in sports activities, tasks of the existing sport system in Ukraine. The legal framework, state legislative acts, materials of state institutions, social polls, conclusions of specialists in the sphere of sports, sports observers are used for the research. The author emphasizes the need of the solution of a number of existing problems at the state level and creations of necessary conditions for sport progress in Ukraine. The use of international practices is suggested and recommendations are given for taking concrete steps in the creation of an effective model for the development of sport that is provided on condition of the active participation of the state and society.